Modélisation économétrique de la relation de l’économie numérique et la croissance économique Algérienne: Econometric modeling of the relationship between the digital economy and Algerian economic growth - TALHA Ahmed; LAMRI Khadidja (Journal of North African Economies, 2025)
The main objective of this article is to analyze the relationship between the digital economy and Algerian economic growth, so that it has become an engine of productivity and competitiveness, represented by fixed telephone subscriptions, mobile cellular subscriptions, and fixed broadband subscriptions as main variables of this modeling during the period 1995-2021. For this purpose, a model was estimated following the econometric methodology that represents the Co-integration of J-J and the study of the existence of a short-run error correction. The results show that the fixed telephone subscriptions has a significant positive effect on economic growth in Algeria, on the other hand the mobile cellular subscriptions and fixed broadband subscriptions have significant negative effects.